1983
DOI: 10.1002/1098-108x(198322)2:4<199::aid-eat2260020429>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Short-term group treatment of bulimia. A Preliminary report

Abstract: This brief report presents preliminary findings regarding the use of short‐term group treatment for bulimia. Ten patients who met the Diagnostic and Statistical Manual III (DSM‐III) criteria for bulimia were treated in a 12‐session psycho‐educational format. Results indicated that all patients reduced the frequency of their bulimic behavior and showed change in attitudes related to pathological eating behavior. The preliminary results suggest that short‐term group treatment may be a moderately effective treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 10 publications
(4 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, the results of this study have demonstrated that inconsistency is an important and neglected feature of the visual judgements about body image, which as Halmi (1983) has noted, may not be the most appropriate way to assess body image disturbances. Multidimensional approaches to anorexia nervosa Andersen, Hedblom, Hubbard, 1983) and to bulimia nervosa (Lacey, 1983;Johnson, Connors, Stuckey, 1983;Huon and Brown, 1984) should also be applied to investigations of the body images of those with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the results of this study have demonstrated that inconsistency is an important and neglected feature of the visual judgements about body image, which as Halmi (1983) has noted, may not be the most appropriate way to assess body image disturbances. Multidimensional approaches to anorexia nervosa Andersen, Hedblom, Hubbard, 1983) and to bulimia nervosa (Lacey, 1983;Johnson, Connors, Stuckey, 1983;Huon and Brown, 1984) should also be applied to investigations of the body images of those with these disorders.…”
Section: Discussionmentioning
confidence: 99%
“…One outcome study which combined insight and behavioral techniques in both individual and group treatment reported a decrease in bulimic behaviors (Lacey, 1983). Those researchers who advocate the merits of specific treatments; individual psychotherapy (Crisp, 1981-82;Johnson, Conners & Stuckey, 1983), inpatient hospitalization (Halmi, 1982), and nutritional education (Lucas, 1983) and structured cognitivehehavioral programs (Orleans & Barnett, reference note 1; Coffman, reference note 2; Long, 1982), have yet to demonstrate in an empirical manner the long-term outcome of the illness and/or the relationship of the sociaYpsychologica1 symptoms with behavioral changes in the eating patterns. One outcome study that has assessed psychological change with treatment in normal-weight bulimia was conducted by Boskind-Ledahl and White (Boskind-Lodahl & White, 1976;Boskind-Lodahl & White, 1978).…”
mentioning
confidence: 99%
“…Results of the present study indicate that there was, for the entire sample, a significant reduction in both bingeing and vomiting from pre-to posttest, corroborating other studies that have found short-term group treatment for bulimia effective (e.g., Johnson et al, 1983;Lacey, 1983; Kirkley et al, 1985). On further inspection, these results demonstrate that those whose symptomatology was most severe at onset, as a group, showed the greatest reduction in bulimic symptomatology at the conclusion of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although several of the studies cited (Johnson et al, 1983;Stevens & Salisbury, 1984) report the number of binge/purge episodes per week, per subject pre-and posttreatment, the actual effect of shortterm group treatment on binge/purge behavior has not been studied in relation to the severity of symptom behavior at the onset of treatment. The majority of the studies cited report their findings as overall percent decreases in symptomatology, which as an outcome measure may tend to obscure different patterns of symptom change that may exist in relation to the presenting severity of symptomatology at the onset of treatment.…”
mentioning
confidence: 99%